The Role of Social Institutions in the Social Development of Transmigrant Communities in Jambi 1983-2006 - Simatupang, Novia Roza; Arianti, Amelda; Garadian, Endi Aulia (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study discusses social institutions in the social, cultural, and economic advancement of transmigrant communities in the Durian Luncuk I Transmigration Settlement Unit (UPT) - Jangga Baru Village, Jambi Province, in the period 1983-2006. Transmigration in Durian Luncuk was carried out using the PIR (People's Core Plantation)-Special pattern, which received social guidance from the Department of Transmigration and Economics from PTPN VI Durian Luncuk. This study uses a historical method of heuristics, verification, interpretation, and historiography. Primary data were obtained through interviews, written documents, and archives obtained from the Regional Library and the National Library, in the form of research report monographs, and newspaper articles. The results of the study indicate that social institutions, both formal and non-formal, such as farmer groups, KUD, markets, social gatherings, mosques, and art groups play an important role in improving the economic level, and socio-cultural advancement of transmigrant communities, in addition, social institutions also play a role in building harmonious interactions among heterogeneous transmigrants. In other words, social institutions are important capital in the success of the transmigration program.